Dual Band-Notch Small Square Monopole Antenna with Enhanced Bandwidth Characterestics for UWB Applications - Ojaroudi, M.; Ojaroudi, N.; Ebazadeh, Y. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
This article proposes a novel printed monopole antenna for ultra wideband applications with dual band-notch function. The antenna consists of a square radiating patch with four rectangular slits and a ground plane with a pair of T-shaped parasitic structures, which provides a wide usable fractional bandwidth of more than 165% (2.79-14.83 GHz). In order to generate single band-notch characteristics, we use two rectangular slits in the corners of square radiating patch. By adding two rectangular slits in the center of the modified radiating patch, a dual band notch function is achieved and also by inserting a pair of T-shaped parasitic structures in the ground plane, additional resonances are excited and hence much wider impedance bandwidth can be produced, especially at the higher band. The measured results reveal that the presented dual band-notch monopole antenna offers a very wide bandwidth with two notched bands, covering all the 5.2/5.8GHz WLAN, 3.5/5.5 GHz WiMAX and 4- GHz C bands. The designed antenna has a small size of 12×18 mm2 .